Primary Rhegmatogenous Retinal Detachment Surgery in Modern Era - Awan, Amer (Pakistan Journal of Ophthalmology, 2018)
Rhegmatogenous retinal detachment (RRD) is a common clinical challenge that affects up to one of every 170 people1. RRD is one of the most common indications for vitreoretinal surgery. Jules Gonin treated the first case of idiopathic retinal detachment with a clear media on 16 October 1916 and the outcome was successful. Gonin subsequently reported on his first 300 cases (1929–1931) and quoted a success rate of 39%2. RRD surgery is somewhat different among ophthalmic surgeries because excellent outcomes may be achieved using three distinct approaches: scleral buckling (SB), first described in 1950s3,4, pars plana vitrectomy (PPV) first reported in 19715 and pneumatic retinopexy (PR) first reported in 19866. However, the main principles in RRD management include identification and treatment of all retinal breaks7.